2020
DOI: 10.3390/molecules25081775
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Pharmacokinetics of SP-8356, a Novel (1S)-(−)-Verbenone Derivative, in Rats and Dogs and Its Implications in Humans

Abstract: (1S,5R)-4-((E)-3,4-dihydroxy-5-methoxystryryl)-6,6-dimethylbicylco[3.1.1]hept-3-en-2-one (SP-8356) is a novel (1S)-(−)-verbenone derivative that is currently in preclinical development for the treatment of ischemic stroke and atherosclerosis. This report aimed at characterization of the metabolism and pharmacokinetic properties of SP-8356. Following intravenous dose in rats and dogs, plasma concentrations of SP-8356 declined rapidly with high clearance (CL) and short half-life; after oral administration in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…We found that the E H of rat was higher than that of human. This result is reasonable, judging from t 1/2 values, because rat liver has been reported to metabolize faster than human liver [28]. Compared with other compound reports using rat liver S9, GKB202 of the Antrodia cinnamomea mycelium (t 1/2 = 3.68 min) was metabolized more rapidly than erinacine A [29].…”
Section: Quantification Of Erinacine a In Rat And Human Liver S9 Anal...supporting
confidence: 67%
“…We found that the E H of rat was higher than that of human. This result is reasonable, judging from t 1/2 values, because rat liver has been reported to metabolize faster than human liver [28]. Compared with other compound reports using rat liver S9, GKB202 of the Antrodia cinnamomea mycelium (t 1/2 = 3.68 min) was metabolized more rapidly than erinacine A [29].…”
Section: Quantification Of Erinacine a In Rat And Human Liver S9 Anal...supporting
confidence: 67%
“…Based on previous studies by Zhou et al [ 39 ] and Lee et al [ 40 ], we designed an in vitro incubation test. BUS is an anti-anxiety medication that alters brain chemicals that may be out of balance in persons who suffer from anxiety.…”
Section: Resultsmentioning
confidence: 99%